Pengetahuan Biaya Lingkungan dan Konsep Green Accounting pada Hotel Klasifikasi Melati di Kota Surakarta - Siti Zulaikhah; Endah Kristiani (Media Akuntansi, 2020)
This study aims to determine how knowledge of environmental costs and the concept of green accounting is implemented in hotels classified as Melati in the city of Surakarta. The sample in this study were 30 hotels classified as Melati in the city of Surakarta. This research method uses the Instrument Quality test, Description Analysis and Variable Description Analysis. The study used a questionnaire distributed within a period of 1 month. The results showed that hotel managers classified as Melati lacked knowledge of environmental costs and the concept of green accounting which had to be implemented properly. Hotels classified as Melati still consider service quality as a top priority in management indicated by (1) environmental care only related to expenses for waste from business results, but not offset by the use of environmentally friendly equipment, (2) awareness of environmental costs by knowing costs that must be issued to treat business waste but do not yet have good knowledge of the required environmental costs, (3) have cost knowledge of the components of hotel business costs but do not yet know how to manage business costs, (4) knowledge of environmental costs by charging environmental costs into business costs, but said respondents do not know the components of environmental costs and (5) the style of expenditure of individuals who are very thrifty by always checking the existing hotel cash when deciding to buy something and not make expenditures in vain. Knowledge of environmental costs and the concept of green accounting must begin to be socialized not only to large-scale (starred) hotel managers, but also to small-scale (non-star / Melati) hotel managers.